As South Africa's cities burn: we can clean-up, but we cannot sweep away inequality. Issue 10 (3rd October 2021) - Kalina, Marc
ABSTRACT: In July 2021, large swathes of South Africa experienced several days of intense violence and looting, nominally stemming from political causes, but rooted more deeply in spiraling inequality and growing poverty. As the violence slowed, the "clean-up", began immediately, with South Africa's citizens banding together to sweep away the collected waste and debris left behind. Yet, as South Africa's most populous provinces burned, the detritus of their destruction is another poignant reminder that without addressing growing inequality, both domestically and globally, it will always be one-step forward, two-steps backwards for trying to create cleaner communities and to solving our interconnected waste management and climate change challenges. Written in the aftermath of July's events, the purpose of this viewpoint is to call for a centering of inequality within waste management academic discourse. Inequality, and its causes, must move from the fringe, to the mainstream within our collective body of work. Specifically, we must continuously, and meaningfully, engage with the systemic socio-economic and socio-political conditions responsible for our waste problems if we are to address them. Moreover, we, as academics should always be mindful of the ways in which our work relates to, or possibly contributes to, inequality, through (in)accessibility within communities or to systemic inequalities between the Global North and the Global South.